Contribution of Cеsare Lombroso in the development of criminology - Pylypchuk, O. O. (History of science and technology, 2017)
The article is devoted to milestones of life and work of the Italian scientist Cesare Lombroso (1835-1909), who went down in history as the founder of legal science of criminal anthropology. He first formulated the theory that the main object of study should be criminal and the crime without considering the identity of the perpetrator is simply unfounded facts. He determined physiological and psychological features of a particular type of «criminal person.» He was convinced that the physiological features of person and his ability to commit crimes can be combined on the principle of «cause-consequence».